The Impact of Multisectoral Nutrition Interventions on Stunting Rates Among Children Under Five Years Old: A Systematic Review - Andrian Dwi Rizki Setyawan; Titik Setyawan; Edy Sucipto (The International Journal of Medical Science and Health Research, 2025)
Introduction: Childhood stunting, defined as impaired linear growth, is a profound public health crisis affecting millions of children globally. It results from chronic undernutrition and leads to irreversible cognitive and physical deficits, perpetuating a cycle of poverty and diminished human capital. The complex, multifactorial etiology of stunting necessitates a shift from siloed, nutrition-specific actions to integrated, multisectoral interventions that address its underlying determinants. This systematic review synthesizes the evidence on the effectiveness of combining interventions from sectors such as health, water and sanitation (WASH), agriculture, social protection, and education to reduce stunting rates among children under five. Methods: A systematic search of major electronic databases (including PubMed, Semanthic Scholar, Google Scholar, Springer, Wiley Online Library) was conducted to identify studies published up to 2025. Randomized controlled trials (RCTs) and quasi-experimental studies evaluating the impact of multisectoral interventions (defined as combining nutrition-specific components with at least one nutrition-sensitive component) on stunting and related outcomes in children aged 0–59 months were included. Data were extracted for over 15 outcomes, including anthropometry, morbidity, and dietary practices. Study quality was assessed using appropriate risk-of-bias tools. Random-effects meta-analysis was used to pool effect sizes where appropriate. Results: The review identified a robust body of evidence demonstrating the superiority of multisectoral approaches. The integration of WASH and nutrition interventions showed a significant positive effect on Height-for-Age Z-score (HAZ) (MD=0.13; 95% CI 0.08 to 0.17) and Weight-for-Age Z-score (WAZ) (MD=0.09; 95% CI 0.05 to 0.13). Nutrition-sensitive agriculture programs consistently improved intermediate outcomes like child dietary diversity but had a less consistent direct impact on stunting. Social protection, primarily through cash transfers, yielded a modest but significant reduction in stunting prevalence (−1.35%; 95% CI -2.35 to -0.35), with effects amplified when combined with behavior change communication (BCC). Across all sectors, BCC emerged as a critical enabler, significantly improving maternal practices and child growth. However, interventions proven effective in rural settings often failed in urban slums, highlighting severe contextual implementation challenges. Discussion: The findings confirm that synergistic action across sectors is more effective than isolated interventions. The mechanisms of impact align with the UNICEF conceptual framework, where different sectors address distinct underlying and immediate determinants of malnutrition. While the evidence for multisectoral approaches is strong, the overall magnitude of effect on stunting is often modest, suggesting that longer intervention periods and higher intensity may be required to reverse chronic deficits. The failure of programs in urban slums points to an "implementation efficacy gap," where the context, rather than the intervention itself, is the primary barrier to success. Conclusion: Multisectoral nutrition interventions represent the most effective strategy for accelerating stunting reduction. Policy and funding mechanisms must shift to support integrated program design and cross-ministerial collaboration. Future programs should prioritize the bundling of nutrition, WASH, and social protection interventions, with a robust BCC component as a non-negotiable catalyst for success. Further research is urgently needed to develop and evaluate context-specific delivery models for vulnerable populations, particularly in urban slums.